Characterization of Drugs with Good Glass Formers in Loaded-Mesoporous Silica and Its Theoretical Value Relevance with Mesopores Surface and Pore-Filling Capacity - Arif Budiman; Diah Lia Aulifa (MDPI AG, 2022)
The incorporation of a drug into mesoporous silica (MPS) is a promising strategy to stabilize its amorphous form. However, the drug within MPS has shown incomplete release, despite a supersaturated solution being generated. This indicates the determination of maximum drug loading in MPS below what is experimentally necessary to maximize the drug doses in the system. Therefore, this study aimed to characterize the drugs with good glass former loaded-mesoporous silica, determine the maximum drug loading, and compare its theoretical value relevance to monolayer covering the mesoporous (MCM) surface, as well as pore-filling capacity (PFC). Solvent evaporation and melt methods were used to load each drug into MPS. In addition, the glass transition of ritonavir (RTV) and cyclosporine A (CYP), as well as the melting peak of indomethacin (IDM) and saccharin (SAC) in mesoporous silica, were not discovered in the modulated differential scanning calorimetry (MDSC) curve, demonstrating that each drug was successfully incorporated into the mesopores. The amorphization of RTV-loaded MPS (RTV/MPS), CYP-loaded MPS (CYP/MPS), and IDM-loaded MPS (IDM/MPS) were confirmed as a halo pattern in powder X-ray diffraction measurements and a single glass transition event in the MDSC curve. Additionally, the good glass formers, nanoconfinement effect of MPS and silica surface interaction contributed to the amorphization of RTV, CYP and IDM within MPS. Meanwhile, the crystallization of SAC was observed in SAC-loaded MPS (SAC/MPS) due to its weak silica surface interaction and high recrystallization tendency. The maximum loading amount of RTV/MPS was experimentally close to the theoretical amount of MCM, showing monomolecular adsorption of RTV on the silica surface. On the other hand, the maximum loading amount of CYP/MPS and IDM/MPS was experimentally lower than the theoretical amount of MCM due to the lack of surface interaction. However, neither CYP or IDM occupied the entire silica surface, even though some drugs were adsorbed on the MPS surface. Moreover, the maximum loading amount of SAC/MPS was experimentally close to the theoretical amount of PFC, suggesting the multilayers of SAC within the MPS. Therefore, this study demonstrates that the characterization of drugs within MPS, such as molecular size and interaction of drug-silica surface, affects the loading efficiency of drugs within MPS that influence its relevance with the theoretical value of drugs.